Water-dispersible polyurethane systems used as pressure-sensitive adhesives - Czech, Z.; Koćmierowska, M. (Polimery, 2022)
Water-dispersible polyurethane systems based on anionic polyurethane aqueous dispersions were obtained. The prepolymers besed on hydroxyl-termined polybutadiene (HTPB), isophorone diisocyanate (IPDI), poly(propylene glycol) (PPG) and dimethylopropionic acid (DMPA) were synthesized in bulk. After neutralization with triethyleneamine (TEA) the anionomer prepolymer was dispersed in water, followed by a chain-extension reaction with ethylenediamine (EDA). The adhesive and cohesive properties of aqueous dispersions as coatings for self-adhesive articles were evaluated. It was observed that DMPA and crosslinking agent contents as well as kind of poly(propylene glycol) influenced adhesion and cohesion of polyurethane films.